CMEs in the heliosphere: III. a statistical analysis of the kinematic properties derived from stereoscopic geometrical modelling techniques applied to CMEs detected in the heliosphere from 2008 to 2014 by STEREO/HI-1 - Barnes,D; Davies,JA; Harrison,RA; Byrne,JP; Perry,CH; Bothmer,V; Eastwood,JP; Gallagher,PT; Kilpua,EKJ; Möstl,C; Rodriguez,L; Rouillard,AP; et al. (Solar Physics: a journal for solar and solar-stellar research and the study of solar terrestrial physics, 2020)
We present an analysis of coronal mass ejections (CMEs) observed by the Heliospheric Imagers (HIs) onboard NASA’s Solar Terrestrial Relations Observatory (STEREO) spacecraft. Between August 2008 and April 2014 we identify 273 CMEs that are observed simultaneously, by the HIs on both spacecraft. For each CME, we track the observed leading edge, as a function of time, from both vantage points, and apply the Stereoscopic Self-Similar Expansion (SSSE) technique to infer their propagation throughout the inner heliosphere. The technique is unable to accurately locate CMEs when their observed leading edge passes between the spacecraft; however, we are able to successfully apply the technique to 151, most of which occur once the spacecraft-separation angle exceeds 180, during solar maximum. We find that using a small half-width to fit the CME can result in inferred acceleration to unphysically high velocities and that using a larger half-width can fail to accurately locate the CMEs close to the Sun because the method does not account for CME over-expansion in this region. Observed velocities from SSSE are found to agree well with single-spacecraft (SSEF) analysis techniques applied to the same events. CME propagation directions derived from SSSE and SSEF analysis agree poorly because of known limitations present in the latter.